EPI Coverage among Under 5 Children Attending Pediatric Department of Dhaka Medical College Hospital - Shoma, Farah Naz; Shah, Nadim Ahmed; Sarker, Mst Naznin; Islam, M M Shahin Ul; Saad, Tania; Mollah, Abid Hossain (Faridpur Medical College Journal, 2013)
This cross-sectional study was carried out among 1000 children between 10 months to 5 years of age during November 2004 to February 2005 attended in the department of pediatrics, Dhaka Medical College Hospital (DMCH) with different childhood illness. Aim of study was to know the Immunization (EPI) coverage, dropout rate and factors influencing dropout. According to parent's statement, 82.5% of the children were fully, 16.1% were partially and 1.4% were non-immunized. Specific immunization coverage revealed that, 97.3% were immunized with BCG, 96.7% with DPT1/OPV1, 92.9% with DPT2/OPV2, 91% with DPT3/OPV3 & 84% with measles vaccine. Among the BCG vaccinated children 91.77% had BCG scar. Drop out of DPT1-DPT3 was 5.78% & DPT1- measles was 12.88%. The main reason found for non-immunization were lack of faith in programme (57.1%), lack of awareness (21.4%), and fear of side effects (21.4%), whereas lack of awareness (41.6%) and illness of child (32.9%) played role behind drop out. Drop out cases were found to be associated with female sex, parent's illiteracy, higher number of children in the family and father's occupation (p<0.001), whereas mothers occupation had no independent effect on coverage (p>0.05). The study findings suggested that despite the effort taken by Government and NGOs to expand coverage, dropout rates are unacceptably high. To combat this challenge counseling and motivation on EPI, improvement of information system, health education and training of health workers are required. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13499 Faridpur Med. Coll. J. 2012;7(2): 59-62